Pengaruh Variasi Delignifikasi NaOH dan Variasi Hidrolisis H2SO4 Terhadap Produksi Bioetanol dari Limbah Umbi Porang Menggunakan Saccharomyces cerevisiae - Toety Marliaty; Adrianto Ahmad; Bahruddin Bahruddin (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2026)
Second-generation bioethanol from non-food biomass requires pretreatment and hydrolysis conditions that increase fermentable sugar release while keeping the hydrolysate suitable for fermentation. This study evaluated the effects of NaOH delignification (1–2% v/v) and dilute H₂SO₄ hydrolysis (0.25–0.75% v/v) on sugar formation and ethanol production from porang tuber waste using Saccharomyces cerevisiae. Porang chips (60 mesh) were pretreated at 100°C for 60 min at a 1:10 (w/v) solid-to-liquid ratio, washed to near-neutral pH, and subsequently hydrolyzed at 100°C for 60 min at 1:20 (w/v). Structural carbohydrates were quantified by the Chesson–Datta method, reducing sugars by UV–Vis spectrophotometry, and ethanol by distillation followed by refractometry. NaOH at 1.5% resulted in the most favorable compositional change, increasing cellulose to 55.3% and reducing lignin to 7.0%. The highest initial glucose in the hydrolysate (41.22 g/L) and the best ethanol performance were obtained at NaOH 1.5%–H₂SO₄ 0.5%, reaching 8.62 g/L ethanol, a yield (Yp/s) of 0.434 g/g, and 85.0% of the theoretical yield. Overall, within the tested NaOH–H₂SO₄ ranges, moderate pretreatment and hydrolysis levels provided a practical balance between sugar release and fermentation performance at bench scale. Measurement variability and uncertainty (replicates and dispersion metrics) are reported in the Results to support the observed trends